2019
DOI: 10.1016/j.polymer.2018.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the heat transfer by conduction of nanocellular polymers with bimodal cellular structures

Abstract: A model to predict the thermal conductivity of nanocellular polymers is presented. • This model applies to nanocellular materials with non-uniform cellular structures. • The thermal conductivity of bimodal systems with nanometric cells is predicted. • The model is validated using experimental results of real bimodal systems. • It can be also applied to nanocellular polymers with wide cell size distributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
(81 reference statements)
0
26
0
Order By: Relevance
“…For low-pressure FIM the resulting component weight-saving is lower however the cell structure of high-pressure foaming shows better microcellular structure [12]. Towards nano-cellular microstructure has proven to improve thermal conductivity due to the Knudsen effect [13,14], improved relevant mechanical strength along with more consistent final parts [15].…”
Section: Introductionmentioning
confidence: 99%
“…For low-pressure FIM the resulting component weight-saving is lower however the cell structure of high-pressure foaming shows better microcellular structure [12]. Towards nano-cellular microstructure has proven to improve thermal conductivity due to the Knudsen effect [13,14], improved relevant mechanical strength along with more consistent final parts [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the thermal conductivity of PBS samples was decreased from 192 ± 3 to 119 ± 5 mW·(m·K) −1 by the foaming process. Bernardo et al [58] reported that the presence of microcells in polymer foams allowed decreasing thermal conductivity through the conduction of solid phase, while nanocells in polymer foams could contribute to decreasing the thermal conductivity via the conduction of gas phase. Besides, the thermal conductivity of gas phase was remarkably decreased in the nanocellular polymer foams compared with that in the microcellular polymer foams due to the reduction of cell size from 1 μm to 100 nm, thus nanocellular CPBS foams have a better thermal insulation property, compared with microcellular PBS foams [2].…”
Section: Resultsmentioning
confidence: 99%
“…Industries such as the automotive one or the building sector could improve their current designs by using these materials. However, so as to take advantage of properties, such as the thermal insulation, it is mandatory to reduce the density of the cellular material in addition to the cell size [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%